». . . der Bund und Treue hält ewiglich« - Hofheinz, Marco (Zeitschrift für Theologie und Kirche, 2020)
In the local theological ethics discourse a covenantal silence is spreading. This is in contrast to the forced speech on covenant, for example in the reformed history of piety, culture and ideas, as well as in the public omnipresence of the concept of covenant as a basic metaphor of the social and political. The present study is, as it were, a sign of loss, in that it traces some of the modern development of the transformation from a biblically grounded federal theology to a horizontal contractualism. As the thesis contends, this modern contract theory can be understood as a docked federal theology, which substituted the covenant of God with a social contract. The essay draws from Karl Barth's approach to covenant theology and his freedom-theoretical conception of the covenant as a covenant of grace to challenge this problematic historic development. The reflection addresses a fundamental question: What was lost when the covenant became a contract?